A miniature illumination probe in lightsheet fluorescence microscopy for real-time imaging injured adult zebrafish’s ventricular recuperation - Ho-Ching Hsiao; Po-Sheng Hu (International Journal of Optomechatronics, 2024)
Imaging adult zebrafish’s cardiac organ is often hampered by the limited volume of the internal cavity. This research study aims to design, manufacture and apply a miniature illumination probe amended with an aluminum-coated polydimethylsiloxane (PDMS) concave cylindrical mirrors as well as 3D-printed casings for probe assembly in a light-sheet fluorescence microscopy to explore its applicability of visualizing adult zebrafish’s ventricle. The system was calibrated and characterized. The experimental results successfully demonstrated the tracking of the ventricular regeneration in female adult zebrafish at multiple time points and can be conducive to other heart-related research in in vivo settings.